The effects of gamma irradiation on physico-chemical and sensory attributes of fresh carabao-mango (Mangifera indica L.) - Baral, Madhav P.; Alabastro, Estrella F. (1989)
An investigation on the physical, physiological, chemical and sensory properties of three lots of fresh irradiated (50 and 75 krad) and unirradiated carabao mangoes with or without heat treatment (50°C for 5 minutes) prior to irradiation was made during post-harvest storage at ambient temperature. The three lots of mangoes were obtained from three sources (Bulacan, Batangas and Cebu) at different times of the year (May, June and August). Analysis of variance results revealed significant differences in physical and physiological properties, namely, weight loss, delay in ripening, respiration rate and marketability, of irradiated and unirradiated mangoes. Mangoes irradiated at 50 krad which had undergone hot water treatment at 50°C for 5 minutes had maximum storage life compared to other treatment groups. Storage time and lot had also significant effects on the above parameters. The chemical parameters measured in the mango pulp during storage were: pH, titratable acidity, total soluble solids, carotene, ascorbic acid, starch, reducing sugars, and pectin content. The results showed no significant differences in above chemical properties/components among the control, heat treated, irradiated, and heat treated plus irradiated fruits. However, storage time and lot had significant effects on these chemical properties/components of mangoes during the ripening. A significant difference in pectinesterase (PE) enzyme activity was observed between irradiated and non-irradiated mangoes. Irradiated mangoes had higher PE activities than control and heat treated mangoes. There was a significant loss in PE activity during storage in both the irradiated and unirradiated mangoes. No PG activities were detected up to 12 days of storage. Polyphenol oxidase (PPO) activities were not detected in both irradiated and unirradiated fruits during the initial stage of ripening, but were detectable at a later stage. However, irradiated fruits showed some PPO activity earlier than unirradiated fruits. Although PPO was present in the ripening mango, no discoloration browning on the skin of the fruits was observed. Distillates of both irradiated and unirradiated ripe carabao mangoes were yellow, very viscous liquids with pleasing effervescence. Twelve volatile components were isolated from both irradiated and unirradiated mangoes. No major changes in flavor components were observed due to irradiation. No undesirable effects on the sensory characteristics of irradiated and unirradiated mangoes were detected up to 12 days of storage.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Keywords: Mango -- Philippines; Mango -- Effect of gamma irradiation on